Avaliaçao agronômica da Cratylia argentea na zona da Mata de Minas Gerais - Xavier, Deise Ferreira; Carvalho, Margarida Mesquita (International Center for Tropical Agriculture, 1996)
The Zona da Mata region of Minas Gerais, Brazil, is characterized by mountainous topography, the presence of low fertility, highly acidic red-yellow latosols, and the predominance of naturalized pastures of molasses grass (Melinis minutiflora). In studies carried out in the area, Cratylia argentea showed slow initial growth but, after establishment, produced high amounts of dry matter, with a crude protein content between 20 percent and 28 percent. In the greenhouse, C. argentea gave a significant response to the application of phosphorus; the application of lime reduced the requirements of phosphorus during establishment